Effects of intermittent flows on turbine gas meters accuracy. (June 2015) - Cascetta, Furio; Rotondo, Giuseppe
Highlights: Effects of flow pulsations on turbine gas meters accuracy has been investigated. A sample of 21 G250 gas turbine meters has been tested and monitored in field. 17 gas turbine meters have shown " pathological " errors. Abstract: Axial turbine gas meters are well known and appreciated instruments for custody transfer metering, when used at suitable conditions (steady-flow). In anomalous flow conditions (no steady state conditions), with perturbations in the flow (i.e. pulsating flows or intermittent flows), the metrological performance of turbine meter can dramatically decady, inducing remarkable systematic errors. In particular, in the case of intermittent on/off flow (i.e. when the flow is abruptly shut off by means of a valve) the turbine wheel slows down after the flow has stopped and consequently a gas volume is measured which is always higher than that which has actually flown through the gas meter. In this paper, in order to determine the actual behavior of turbine gas meter under intermittent on/off flow conditions, a field test has been carried out: a sample of G250 size gas turbine meters has been tested and monitored with the aim to assess the average overestimated gas volumes and the consequent percentage stop delay errors. In addition new original formulae allowing to estimate the percentage error e (%) as a function of the running time ( t ) for a fixed flow rate (0.1 Q max ), are provided.